The Contribution of Mahabbah to Academic Stress Levels Students - Burhani, Muhammad; Fadhila, Mahdia (Empathy : Jurnal Fakultas Psikologi, 2023)
Kontribusi Mahabbah terhadap Tingkat Stres Akademik Mahasiswa Everyone has problems, including students. Students can experience academic stress due to the pressure in college. Islam says stress occurs if someone is far from Allah, it makes a feeling of heaviness because there's no way out of problems in his life. To handle this problem it needs to improve mahabbah with Allah to feel closeness with God who created and determined his destiny. This study determines mahabbah's contribution to academic stress at UIN Antasari Banjarmasin students. This research is quantitative with a simple linear regression model analysis. The population in this research is 10.857 active undergraduate students at UIN Antasari Banjarmasin with a sample 340 students. Data collection uses mahabbah and academic stress scale with a Likert Scale. The sampling technique is probability sampling. Data analysis using IBM SPSS Statistics 25. The result showed a significant contribution of mahabbah to academic stress at UIN Antasari Banjarmasin students.